SOCIALIZATION OF AEROBIC EXERCISE FOR ADOLESCENT: IMPROVING PHYSICAL AND MENTAL HEALTH OF ADOLESCENT IN THE DIGITAL ERA - Arfanda, Poppy Elisano; Aprilo, Ians; Mappaompo, M. Adam; Retno Farhana Nurulita; Arimbi (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2024)
Aerobic exercise socialization is designed to improve adolescents' physical and mental fitness in the challenging digital era. This activity involved 76 adolescents in Makassar with a focus on educating the benefits of aerobic exercise, practicing basic movements, and promoting an active lifestyle. Pretest-posttest evaluations showed increased participants' understanding and skills related to the benefits of aerobic exercise. This program succeeded in forming independent and group exercise habits, supported by interactions through social media groups as a platform for sharing experiences. The results of the activity showed that aerobic exercise not only had an impact on improving cardiorespiratory fitness but also mental health, including reducing stress and improving mood. This activity underscores the importance of physical activity in supporting adolescent well-being holistically.